Penambahan inulin terhadap indeks glikemik dan beban glikemik cookies growol: pengembangan makanan selingan diabetes - Desty Ervira Puspaningtyas; Cornelia D.Y. Nekada; Puspita Mardika Sari (AcTion: Aceh Nutrition Journal, 2022)
The increasing prevalence and mortality of diabetes require appropriate treatment, one of which is eating arrangements. The snack development for diabetic patients has begun. Previous studies have developed growol, cassava fermented food, into cookies, but growol cookies still have a high glycemic index (GI). Adding inulin to growol cookies is thought to reduce cookies' GI, which will affect the glycemic load (GL). This study examines the effect of adding inulin to the GI and GL of growol cookies. An observational laboratory design was used to assess the GI and GL of modified growol cookies compared to standard foods (glucose). The study was conducted from June to November 2021 and involved 10 healthy subjects. The total area under the curve (IAUC) was used to calculate the GI of modified growol cookies. The GL was obtained by multiplying the GI by the number of available carbohydrates per serving. Independent Sample T-Test was used to analyze IAUC differences between glucose and modified growol cookies with a significant level of 95% (p<0,05). The IAUC for glucose and modified growol cookies was 4830 and 1995, respectively. There was a difference in the IAUC between glucose and modified growol cookies (p= 0,005). Modified growol cookies have a low GI (41) and low GL if consumed as much as 10-40 grams. Based on GI and GL values, modified growol cookies can be used as a snack for people with diabetes.